Some reflections on the use of administrative data to estimate the net impacts of workforce programs in Washington State - Kevin Hollenbeck (W.E. Upjohn Institute for Employment Research, 2004)
The purpose of this paper is to reflect on the results, methodology, and processes used in a series of net labor market impact studies done for the State of Washington over the past six years. All of the studies relied on administrative data and used a technique referred to as quasi- experimental evaluation. The program interventions were the federal- and state-funded workforce development programs. The paper sets out eight reflections for analysts and policy makers to consider. These reflections identify lessons learned and uncertainties or issues that need more consideration and scrutiny.
Keywords: J24; J31; I28; C93; 330; Berufsbildungspolitik; Lohn; Beschäftigungseffekt; Statistische Methode; Test; Washington (Staat)